The Importance of Spatial Risk Mapping for Livestock Systems in Eastern Africa - Paliwal, Ambica (International Livestock Research Institute, 2025)
This study develops a multi-country livestock vulnerability assessment for Eastern Africa, integrating exposure, sensitivity, and adaptive capacity across varied production systems. Using remote sensing, climate data, and contextual indicators, we examine how droughts, heat stress, forage variability, water scarcity, market disruptions, and animal health risks shape vulnerability in Kenya, Ethiopia, Uganda, and Tanzania. Livestock system sensitivity is assessed through biophysical, management, and socio-economic factors, while adaptive capacity reflects households’ access to resources, services, and coping strategies. The results identify regional hotspots of risk and provide a foundation for targeted interventions, early warning integration, and coordinated resilience planning across countries.